2009
DOI: 10.1002/bjs.6459
|View full text |Cite
|
Sign up to set email alerts
|

Association between [18F]fluorodeoxyglucose uptake and prognostic parameters in breast cancer

Abstract: The SUV is a preoperative and non-invasive metabolic factor that relates to some prognostic factors in breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
122
2
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 12 publications
15
122
2
5
Order By: Relevance
“…This tendency has also been reported previously [11][12][13][14][15][16]. Kawamura et al demonstrated that FDG uptake was affected by the number of metabolically active tumor cells [17].…”
Section: Discussionsupporting
confidence: 85%
“…This tendency has also been reported previously [11][12][13][14][15][16]. Kawamura et al demonstrated that FDG uptake was affected by the number of metabolically active tumor cells [17].…”
Section: Discussionsupporting
confidence: 85%
“…Clinical studies have also found a positive correlation between Ki67 staining and uptake of 18 F-FDG in BC (31)(32)(33)(34), although this relationship is not well defined for lobular carcinoma, which has lower uptake of 18 F-FDG than does ductal carcinoma (31)(32)(33)35). Clinically, most data suggest there is no relationship between HER2 expression evaluated by immunohistochemical staining and tumor uptake of 18 F-FDG (32)(33)(34)36). Only Ueda et al found a positive correlation between expression of HER2 and tumor uptake of 18 F-FDG (35).…”
Section: Discussionmentioning
confidence: 99%
“…However, 39% of patients had clinical stage T1. Given the limited spatial resolution, FDG PET can miss small lesions, and this is especially true for low-grade tumours and lobular carcinoma [10]. In a recent study, among 32 invasive tumours >2 cm, 31 (97%) were well visualized with FDG PET [8].…”
Section: Primary Tumour Assessmentmentioning
confidence: 99%